The role of human fibronectin‐ or placenta basement membrane extract‐based gels in favouring the formation of polarized salivary acinar‐like structures. (3rd May 2016) - Maria, Ola M.; Liu, Younan; El‐Hakim, Michel; Zeitouni, Anthony; Tran, Simon D.
Abstract: Head and neck cancer patients treated with radiotherapy commonly experience hyposalivation and oral/tooth infections, leading to a reduced quality of life. Clinical management is currently unsatisfactory for dry mouth. Thus, there is a need for growing salivary fluid‐secreting (acinar) cells for these patients. However, functionally‐grown salivary acinar cells are cultured in Matrigel, a product that cannot be used clinically, owing to its source from a mouse sarcoma. Therefore, finding a gel suitable for clinical use and possessing properties similar to that of Matrigel would allow biopsied salivary cells to be expanded in vitro and transplanted into the mouths of xerostomic patients. This study tested gels made with human placenta basement membrane extract (BME) or fibronectin for the growth and differentiation of human salivary biopsies into acinar cells. We report here that, following expansion of primary human salivary gland epithelial cells (huSGs) in serum‐free medium, using these gels (made from human proteins) allowed morphological and functional differentiation of salivary ductal cells into acinar‐like cells. These (human) gels gave comparable results to Matrigel, such as differentiation into polarized acinar 3D units or monolayers with tight junction proteins (claudin‐1, ‐2, ‐3) and exhibiting adequate transepithelial electrical resistance, acinar proteins (AQP5, α ‐amylase, mucin‐1, NKCC1) and acinar adhesion‐related cell markers (CD44, CD166). Ultrastructural, mRNA and protein analyses confirmed the formation of differentiated acinar polarized cells. The mitotic activity was highest with human placenta BME gel. This human culture model provided a reproducible approach to studying human salivary cell expansion and differentiation for tissue engineering. Copyright © 2016 John Wiley & Sons, Ltd.